دور النيابة العامة في حماية حقوق الإنسان في التشريع الجزائري - بلال معمري; سليم شرفي (My University, 2025)
Abstract This study examines the crime of child abduction in Algerian law، clarifying its concept and distinguishing it from other crimes. It also examines the factors leading to its spread and its connection with similar crimes، and offers ways to combat and reduce it.The study includes an analysis of the legal systems related to the crime of child abduction and identifies the penalties imposed، which in some cases can reach life imprisonment or the death penalty.Algerian law punishes this crime with felony and misdemeanor penalties، and also punishes attempts and attempts to commit it. It also provides the perpetrator with a way to withdraw by enabling them to benefit from mitigating circumstances. From this، we conclude that the crime of child abduction has become a phenomenon that requires concerted efforts in various fields to combat it and prevent its commission or the commission of similar crimes against children whose only crime is their inability to defend themselves. ....................... ملخص تتناول الدراسة دور النيابة العامة في حماية حقوق الإنسان في التشريع الجزائري، مع التركيز على مراحل الدعوى العمومية قبل وبعد تحريكها. تهدف الدراسة إلى تحليل الإطار القانوني لصلاحيات النيابة العامة وتقييم مدى توافقها مع المعايير الدولية لحقوق الإنسان، مثل الإعلان العالمي لحقوق الإنسان والعهد الدولي للحقوق المدنية والسياسية. كما تسلط الضوء على الآليات الحديثة مثل الوساطة الجزائية كبديل عن المتابعة التقليدية، ودور النيابة العامة في الرقابة على إجراءات الضبطية القضائية لضمان احترام الحريات الفردية. تنقسم الدراسة إلى فصلين رئيسيين: الفصل الأول: يتناول دور النيابة العامة في حماية حقوق الإنسان قبل تحريك الدعوى العمومية، من خلال الرقابة على الضبطية القضائية والتحكم في مصير الدعوى عبر قرارات الحفظ أو الوساطة. الفصل الثاني: يركز على دور النيابة العامة بعد تحريك الدعوى، سواء في مرحلة التحقيق الابتدائي أو أثناء المحاكمة والتنفيذ، مع التأكيد على ضمانات المحاكمة العادلة مثل قرينة البراءة وحق الدفاع. ............................. Résumé Cette étude examine le crime d'enlèvement d'enfants en droit algérien, clarifiant sa notion et le distinguant des autres crimes. Elle examine également les facteurs de sa propagation et ses liens avec des crimes similaires, et propose des solutions pour le combattre et le réduire. L'étude comprend une analyse des systèmes juridiques relatifs au crime d'enlèvement d'enfants et identifie les sanctions prévues, qui peuvent aller jusqu'à la réclusion criminelle à perpétuité ou la peine de mort. Le droit algérien punit ce crime de crimes et de délits, et punit également les tentatives. Il offre également à l'auteur un moyen de se retirer en lui permettant de bénéficier de circonstances atténuantes. Nous concluons ainsi que le crime d'enlèvement d'enfants est devenu un phénomène qui nécessite des efforts concertés dans divers domaines pour le combattre et prévenir sa commission ou la commission de crimes similaires contre des enfants dont le seul crime est leur incapacité à se défendre.
Keywords: Keywords: crime، abduction، child victim، criminal legislation، combating it.; الكلمات المفتاحية: النيابة العامة ، حقوق الإنسان ، التشريع الجزائري ، الوساطة الجزائية ، الضبطية القضائية .; Mots-clés : crime; enlèvement; enfant victime; législation pénale; lutte contre ce crime.